CHARACTERISTICS OF RAW MATERIALS USED TO OBTAIN FINE CERAMICS (Conferencea, 2022)
In this method, the drying time for raw materials is 1-3 days, and for thin items, it takes several hours. In the production of all fine ceramics, 95-97% of the product is formed by the strapping method, and 3-5% of the product is formed by casting in a plaster mold. By means of belt molding, porcelain and earthenware products, insulators, bowls and other fine ceramic products are produced. In this case, the moisture content of the ceramic mass ranges from 17% to 28%, depending on the type of product.